2011
DOI: 10.1016/j.cell.2011.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome-Mediated Specificity in Hox mRNA Translation and Vertebrate Tissue Patterning

Abstract: Historically, the ribosome has been viewed as a complex ribozyme with constitutive rather than regulatory capacity in mRNA translation. Here we identify mutations of the Ribosomal Protein L38 (Rpl38) gene in mice exhibiting surprising tissue specific patterning defects, including pronounced homeotic transformations of the axial skeleton. In Rpl38 mutant embryos, global protein synthesis is unchanged however the translation of a select subset of Homeobox mRNAs is perturbed. Our data reveal that RPL38 facilitate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
555
1
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 537 publications
(597 citation statements)
references
References 70 publications
(67 reference statements)
20
555
1
6
Order By: Relevance
“…One possibility is that individual assembly factors are expressed in a cell type-specific or tissue-restricted manner. A recent report using an Rpl38 mutant mouse described a previously unappreciated enrichment of Rpl38 expression during development in tissues that are affected by its loss (Kondrashov et al, 2011). This also appears to be the case for pes, where tissues with high-level pes expression, including brain, eye and pancreas, are those most severely affected in the pes mutant phenotype (Fig.…”
Section: Research Article Ribosome Biogenesis Genes In Pancreas Develmentioning
confidence: 84%
“…One possibility is that individual assembly factors are expressed in a cell type-specific or tissue-restricted manner. A recent report using an Rpl38 mutant mouse described a previously unappreciated enrichment of Rpl38 expression during development in tissues that are affected by its loss (Kondrashov et al, 2011). This also appears to be the case for pes, where tissues with high-level pes expression, including brain, eye and pancreas, are those most severely affected in the pes mutant phenotype (Fig.…”
Section: Research Article Ribosome Biogenesis Genes In Pancreas Develmentioning
confidence: 84%
“…For example, during initiation on the CrPV IRES, the RNA must associate with rpL1 for subunit joining of the 60S to the 40S and correct ribosome positioning (43,44). Furthermore, by studying mice with a short tail phenotype, rpL38 was found to be required for 80S formation on Homeobox mRNAs and thus correct tissue patterning during development (45). RpL40 is localized on the surface of the ribosome, and its amino and carboxy termini are unblocked, providing potential sites to interact with mRNAs or proteins ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we have demonstrated differences in RP stoichiometry in ribosomes purified from wildtype cells [23], though the functional specificity is implied by a correlation, not shown by direct measurement. Even the prominent example suggesting ribosome specialization, RPL38 regulating HOX genes [39,42], falls short of direct proof since (i) its exclusive specificity to 3 HOX is implied and not directly measured and (ii) the existence of ribosomes lacking RPL38 in wildtype cells is assumed, not measured. However, more recent data from the Barna lab identified distinct mRNA subsets exhibiting enriched or diminished ribosome association with subsets of ribosomes enriched for RPL10a [24], and Ferretti & colleagues demonstrated a specific role for RPS26-containing ribosomes [37].…”
mentioning
confidence: 99%
“…Horos et al, 2012 [38] reported that a single RP, S19, affects the ribosomal density along hundreds of mRNAs essential for the differentiation of murine and human erythroblasts. Other studies also report that RP perturbations can affect the translation of hundreds of genes organized in coherent functional groups [24,39]. RPs are routinely dysregulated in the context of cancer [36,40], and adjusted throughout cell growth and metabolic cycles [41].…”
mentioning
confidence: 99%
See 1 more Smart Citation